2D Materials: Synthesis of 2D Porous Crystalline Materials in Simulated Microgravity (Adv. Mater. 30/2021). Issue 30 (28th July 2021) - Contreras‐Pereda, Noemí; Rodríguez‐San‐Miguel, David; Franco, Carlos; Sevim, Semih; Vale, João Pedro; Solano, Eduardo; Fong, Wye‐Khay; Del Giudice, Alessandra; Galantini, Luciano; Pfattner, Raphael; Pané, Salvador; Mayor, Tiago Sotto; et al.
Abstract : Microgravity has proved to be an ideal condition to grow crystals. In article number 2101777, Raphael Pfattner, Tiago Sotto Mayor, Daniel Ruiz‐Molina, Josep Puigmartí‐Luis, and co‐workers demonstrate how to generate simulated microgravity on Earth to grow 2D porous crystalline molecular frameworks such as 2D metal–organic frameworks and 2D covalent organic frameworks.